Analysis of Arm Muscle Strength on Chestpass Ability in Basketball Games for Students of SMP Negeri 7 Makassar - Nurliani Nurliani; Hasyim Hasyim (STKIP Muhammadiyah Kuningan, 2023)
Analysis of Arm Muscle Strength on Chest Pass Ability in Basketball Games for Students at SMP Negeri 7 Makassar. Department of Physical Education, Health and Recreation, Faculty of Sports Science, Makassar State University. This quantitative descriptive study aims to analyse arm muscle strength on chest pass ability in basketball games for students at SMP Negeri 7 Makassar. The research variable in this study is the independent variable (arm muscle strength) and the dependent variable (chest pass ability). The population in this study were male students in grade VIII in SMP Negeri 7 Makassar, while the sample was 30 students. The data collected in this study included an arm muscle strength test and a chest pass ability test. The data analysis shows a contribution of arm muscle strength to chest pass ability in basketball games for students of SMP Negeri 7 Makassar by 71.3%.